ANTIMIKROBA EKSTRAK ETANOL DAUN TAPAK LIMAN (ELEPHANTOPUS SCABER L.) DENGAMENGGUNAKAN METODE KLT BIOAUTOGRAFI - Faridha Yenny Nonci; Rusli Rusli; Abidah Atqiyah (Jurnal Farmasi UIN Alauddin Makassar, 2014)
Has done research with the title ”Antimicrobial Test Ethanol Leaf Extract Tread Liman (Elephantopus  scaber  L.) by Using Method TLC-Bioautography”. The purpose of this study was to determinethe chemical components and antimicrobial activity of ethanol. The extracts obtanied of leaf by maceration using ethanol 96% solvent. The preliminary research was done by screening test using microbial test to ward ethanol 96% extract of Tapak Liman leaf (Elephantopus  scaber  L.) which where use in 1mg/ml. The result showed that the etanol 96% extract inhibit growth of bacterial Escherchia coli, Pseudomonas aeruginosa, Staphylococcus aureus, dan Vibrio sp. The best obtained from reparation though TLC-Bioautography by means eluen n-hexane : ethyl acetate (3: 1). He results showed that the ethanol extract of leaves of Tread liman (Elephantophus scaber L.) has antimicrobial activity and contains several compounds that have antimicrobial activity.